Prognosis and Risk Factors of Coronary Artery Lesions before Immunoglobulin Therapy in Children with Kawasaki Disease - Huixian Qiu; Chang Jia; Zhenquan Wang; Yuee He; Xing Rong; Rongzhou Wu; Maoping Chu; Hongying Shi (Balkan Medical Journal, 2020)
Background: Many children with Kawasaki disease develop coronary artery lesions before intravenous immunoglobulin treatment. However, little data are available on the prognosis of children with Kawasaki disease who developed coronary artery lesions before intravenous immunoglobulin treatment. Aims: To explore the outcomes of coronary artery lesions before intravenous immunoglobulin treatment in children with Kawasaki disease and analyze the factors that influence the duration of coronary artery lesions. Study Design: Retrospective cohort study. Methods: All patients with Kawasaki disease who developed coronary artery lesions before intravenous immunoglobulin treatment in our hospital from January 2009 to December 2014 were reviewed. A Cox proportional hazards model was used to determine the factors influencing the prognosis of coronary artery lesions. Results: Among 182 patients included, 28.6% were male, 83.50% were younger than 36 months, and 181 exhibited resolution of coronary artery lesions 2 years after disease onset. The median duration of coronary artery lesions was 31 days, and the proportion of coronary artery lesions was 52% at 1 month, 35% at 2 months, 33% at 3 months, 25% at 6 months, 14% at 1 year, and 0.5% at 2 years. The univariate analysis showed that overweight status, higher platelet count, lower albumin level, and starting treatment more than 10 days after disease onset were factors that possibly affect the duration of coronary artery lesions in children. The multivariate Cox regression analysis showed that female sex (adjusted hazard ratio, 1.661; 95% confidence interval, 1.117-2.470) was an independent protective factor, and overweight status (adjusted hazard ratio, 0.469; 95% confidence interval, 0.298-0.737), higher platelet count (adjusted hazard ratio, 0.649; 95% confidence interval, 0.443-0.950), and starting treatment more than 10 days after disease onset (adjusted hazard ratio, 0.392; 95% confidence interval, 0.215-0.716) were independent risk factors for a longer duration of coronary artery lesions. Conclusion: The average duration of coronary artery lesions before intravenous immunoglobulin therapy in children with Kawasaki disease is approximately 1 month. Male gender, overweight status, higher platelet count, and initiation of treatment more than 10 days after the onset of the disease are independent risk factors for longer-lasting coronary artery lesions.